2012
DOI: 10.1111/j.1474-919x.2012.01276.x
|View full text |Cite
|
Sign up to set email alerts
|

Timing of breeding and offspring number covary with plumage colour among GyrfalconsFalco rusticolus

Abstract: Plumage colour variation exists among Gyrfalcons throughout their Arctic and sub-Arctic circumpolar distribution, ranging from white through silver and grey to almost black. Although different colour variants coexist within many populations, a few geographical regions, such as northern Greenland, possess a single variant, suggesting that local environments may influence plumage colour variation. In central-west Greenland (66.5-67.5°N), where multiple colour variants exist, white male Gyrfalcons fathered signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 72 publications
1
5
1
Order By: Relevance
“…A somewhat comparable results was previously reported in regard to productivity by Johnson & Burnham () in gyrfalcons ( Falco rusticolus ) where white males produced earlier clutches and fledged more offspring than darker morphs. As in most raptor species, male black sparrowhawks provide most of the food until the late nestling period, when the female begins to contribute (Ferguson‐Lees & Christie ).…”
Section: Discussionsupporting
confidence: 89%
“…A somewhat comparable results was previously reported in regard to productivity by Johnson & Burnham () in gyrfalcons ( Falco rusticolus ) where white males produced earlier clutches and fledged more offspring than darker morphs. As in most raptor species, male black sparrowhawks provide most of the food until the late nestling period, when the female begins to contribute (Ferguson‐Lees & Christie ).…”
Section: Discussionsupporting
confidence: 89%
“…Hatch (1991) found that reproductive success in northern fulmars Fulmarus glacialis was influenced by the combination of the morph pair, with mixed-pairs exhibiting lower reproductive success than like-pairs. Although Johnson and Burnham's (2013) study on gyrfalcons did not look at productivity of pairs based on their morph consistency, they did find that pairs including a white male bred earlier and had higher productivity (larger clutches and more fledged offspring) than darker morphs. Consistently, found like-pairings in common buzzards produced broods of offspring with lower fitness compared to mixed-pairings and pair combinations involving exclusively extreme morphs (i.e.…”
mentioning
confidence: 94%
“…Roulin's (2004) review highlighted multiple differences in reproductive performance between morphs, with 9 out of 11 species (82%) analysed displaying statistical differences in productivity between morphs. For example amongst diurnal raptors, Johnson and Burnham's () study on gyrfalcons Falco rusticolus in Greenland, found that light morph individuals have earlier clutches and produce more offspring compared to darker grey and silver morphs. Krüger and Lindstrom () found that intermediate morphs of common buzzards display a higher lifetime reproductive success compared to light and dark conspecifics.…”
mentioning
confidence: 99%
“…In blue tit nestlings, the development of both structural (UV/blue) and carotenoid‐based (yellow) plumage has been shown to be associated with nestling body condition and nest environment (Hadfield and Owens ; Hadfield et al. ; Johnson and Burnham ). The effects of nest environment can also impact adult coloration as demonstrated by quantitative genetic studies of bib size in house sparrows ( Passer domesticus ) (Jensen et al.…”
Section: Introductionmentioning
confidence: 99%
“…Early environment is also implicated in causing variation in adult and juvenile plumage coloration. In blue tit nestlings, the development of both structural (UV/blue) and carotenoid-based (yellow) plumage has been shown to be associated with nestling body condition and nest environment (Hadfield and Owens 2006;Hadfield et al 2007;Johnson and Burnham 2013). The effects of nest environment can also impact adult coloration as demonstrated by quantitative genetic studies of bib size in house sparrows (Passer domesticus) (Jensen et al 2006) and plumage color in great tits (Parus major), detectable even after multiple molts (Evans and Sheldon 2012).…”
Section: Introductionmentioning
confidence: 99%